Migration of Midwifery Care Documentation to Medical Records - Liberty Barokah; Dewi Zolekhah; Laili Rahmatul Ilmi (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Medical records are the key to documenting services for health workers who carry out independent practice, good documentation greatly affects the fulfillment of administrative aspects, legal aspects for midwives and patients and provides convenience in maintaining the quality of care documentation to patients. Medical records are very important for health care facilities including Independent Midwife Practices. The function of medical records is to record all health services that have been provided to patients in order to support the improvement of service quality. this study is to implement integrated midwifery care documentation using medical records. The purpose of this study was to implement integrated midwifery care documentation using medical records. This research is an RnD (Research and Development) study with a case study approach. Researchers conducted a data collection process with FGDs. The research was conducted in April-September 2023 at PMB Ummu Hani Bantul Yogyakarta. The object is the recording form that has been implemented. The data validation process used source and technical triangulation. The physical aspect of each form is A4 in size with a weight of 70mg, the paper used for the medical record folder is F4, glossy with cream-colored paper type ivory 260gram. The content aspect includes the division of data items, grouping of data, sequent and how to fill in based on the woman's life cycle, namely grouping the contents for data on pregnant women, maternity, postpartum and children. Obstetric documentation has used integrated documentation from pregnancy to postpartum and child growth and development which has become one document using a medical record folder.